Molecular Characterization of Mercury Binding Ligands Released by Freshwater Algae Grown at Three Photoperiods - Mangal, Vaughn; Phung, Ta; Nguyen, Thien Q.; Guéguen, Celine (Frontiers in Environmental Science, 2019)
Interactions between algal derived dissolved organic matter (DOM) and mercury (Hg) are crucial for understanding the fate, transport, and bioavailability of Hg to methylating microorganisms. For the first time, high resolution mass spectrometry (Q-Exactive Orbitrap) was used to examine Hg binding ligands released by Chlorella vulgaris, Chlamydomonas reinhardtii, and Scenedesmus obliquus grown at three light:dark photoperiods (i.e. 12:12, 16:8 and 20:4 h). van Krevelen diagrams showed a significant increase in carbohydrate and protein DOM and a decrease in released lipid-like molecules as light exposure increased. Hg binding DOM were initially in the form of CHO molecular formulas whereas a shift to higher light durations prompted more Hg to be complexed to CHON and CHONS DOM structures. Despite an overall change in bulk DOM composition, molecular similarities existed in Hg binding DOM as light exposure increased. Hg binding ligands were more similar based on the exposed light duration than based algal species, suggesting growth photoperiods influence Hg binding more than algal taxa. Hg binding DOM at 16:8 and 20:4 h growth cycles were more aromatic and homologous in nature when compared to darker growth conditions that resulted in smaller, more aliphatic Hg-DOM complexes rich in sulphur and thiols. Together, these results highlight the importance of photoperiod on the composition of released DOM and its complexation with Hg.